Maternofetal outcome in early versus late detected asymptomatic bacteriuria of pregnancy - Guntoory, Indira; Penmetsa, Poornima; Rayapu, Sarath B.; Nambaru, Nambaru R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Urinary tract infection in pregnancy is a problem of global significance. Untreated asymptomatic bacteriuria in pregnancy is known to be associated with maternal and foetal outcome in the form of symptomatic urinary tract infection (UTI), acute pyelonephritis, anaemia, pregnancy induced hypertension (PIH), preterm labour (PTL), low birth weight (LBW), intrauterine growth restriction (IUGR) and prematurity. This study is aimed to compare the maternal and foetal outcome of pregnant women with bacteriuria with that of women without bacteriuria and also to see if screening later in pregnancy at 28-37 weeks of gestation is as effective as screening at less than 20 weeks of pregnancy in terms of maternofoetal outcome. Methods: 165 pregnant women attending the antenatal clinic at MIMS, Nellimerla, Vizianagaram district, Andhra Pradesh, India were screened for asymptomatic bacteriuria by urine culture and sensitivity. They were grouped into asymptomatic bacteriuria negative and culture positive groups. Culture positives were further grouped as early detected and late detected group based on the gestational age at sampling. They were followed up till delivery. The maternofoetal outcome was compared between different groups by computing Odd’s ratio and P value of less than 0.05 was taken as significant. Results: There was no statistically significant increase in adverse maternofoetal outcome between early detected and bacteriuria negative group. The women of late detected group had greater odds of developing symptomatic UTI, PIH, PTL, LBW, IUGR and neonatal intensive care unit admissions when compared to early detected and bacteriuria negative group which was statistically significant. Conclusions: Screening for asymptomatic bacteriuria early in pregnancy at less than 20 weeks is more effective in reducing the adverse maternofoetal outcome.